Personality, emotional intelligence and coping styles of conciliators From Arequipa - Arias, Walter (2016)
The present survey analyses the psychological characters of 26 conciliators of an Arequipa city´s group. For this, the personality has been evaluated by the Eysenck Personality Questionnaire, the coping types with the Coping Types Questionnaire by Lazarus and Folkman, the emotional intelligence with the Emotional Intelligence Questionnaire and to value some clinics manifestations of personality we used the MINI-MULT. The results refers that the Arequipa conciliators have sanguine personality in predominant wise, emotional intelligence is higher, and they use the coping, the acceptation of responsibility and the distancing as preferential brave types. We didn’t found significant clinics manifestations. We also found differents relationships between the variables, like between the Neuroticism and some brave types, between Extroversion and Emotional Intelligence, Emotional Intelligence and Autocontrol, between Autocontrol and Acceptation of the own responsibility, between Distancing and Avoidance, between Planning and the Positive Revaluation.